Engineering the next generation of theranostic biomaterials with synthetic biology - Xiang Wang; Qianyi Liang; Yixuan Luo; Jianwen Ye; Yin Yu; Fei Chen (Bioactive Materials, 2024)
Biomaterials have evolved from inert materials to responsive entities, playing a crucial role in disease diagnosis, treatment, and modeling. However, their advancement is hindered by limitations in chemical and mechanical approaches. Synthetic biology enabling the genetically reprograming of biological systems offers a new paradigm. It has achieved remarkable progresses in cell reprogramming, engineering designer cells for diverse applications. Synthetic biology also encompasses cell-free systems and rational design of biological molecules. This review focuses on the application of synthetic biology in theranostics, which boost rapid development of advanced biomaterials. We introduce key fundamental concepts of synthetic biology and highlight frontier applications thereof, aiming to explore the intersection of synthetic biology and biomaterials. This integration holds tremendous promise for advancing biomaterial engineering with programable complex functions.